Embodied Interaction Priority: Other's Body Part Affects Numeral–Space Mappings. (May 2018) - You, Xuqun; Zhang, Yu; Zhu, Rongjuan; Guo, Yu
Traditionally, the spatial–numerical association of response codes (SNARC) effect was presented in two-choice condition, in which only one individual reacted to both even (small) and odd (large) numbers. Few studies explored SNARC effect in a social situation. Moreover, there are many reference frames involved in SNARC effect, and it has not yet been investigated which reference frame is dominated when two participants perform the go-nogo task together. In the present study, we investigated which reference frame plays a primary role in SNARC effect when allocentric and egocentric reference frames were consistent or inconsistent in social settings. Furthermore, we explored how two actors corepresent number–space mapping interactively. Results of the two experiments demonstrated that egocentric reference frame was at work primarily when two reference frames were consistent and inconsistent. This shows that body-centered coordinate frames influence number–space mapping in social settings, and one actor may represent another actor's action and tasks.